Mortality risk and life years lost in young patients with heart failure according ejection fraction. Data from the Swedish Heart failure, National Patient, Cause of Death and Population Registers. (25th November 2020) - Basic, C; Rosengren A, A.R; Dahlstrom, U.D; Edner, M.E; Zverkova Sandstrom, T.Z.S; Schaufelberger, M.S
Abstract: Background: There is a lack of data evaluating excess mortality risk (over that of the general population) and life-years lost in young patients with different heart failure (HF) phenotypes. Purpose: To study excess risk for all-cause mortality in patients <55 years by their ejection fraction (EF) categories and estimate lost "life years" compared to the general population in Sweden. Methods: All patients ≥18 years registered in the national quality register SwedeHF from 2003 to 2014 were included. Patients were divided into ≥55 years and <55 years. For each patient two controls without a HF diagnosis, matched for age, sex and county, were identified from the Swedish Population Register. The use of personal identification number enabled linkage to other registers. All somatic hospital discharge diagnoses are recorded in the National Patient Register (NPR). Time of death and causes of death were obtained from the Cause of Death Register. International Classification of Disease ICD 9 and ICD 10-codes for all co-morbidities were identified in NPR and for underlying causes of death during the observation period from the 1st January 2003 to 31st December 2015. Life expectancy tables from Statistics Sweden were used as reference to the conditional life expectancy for controls calculated at the age 20, 25, 30, 35 and 40 years. Life-years lost were calculated as the difference between conditional life expectancy and conditional survival for patients with HF <55 years presented as median. Results: In total 60, 962 patients, out of whom 3752 <55 years and 7425 controls <55 years were identified. Total observation time was 12 years; median 4.89 years. There were 2549 (67.9%) patients with ejection fraction (EF) <40% and 357 (9.5%) with EF >50%. Patients with HF<40% were more likely to be men (78.2% vs. 56.3%), to have ischemic heart disease (16.9% vs. 2.3%) and dilated cardiomyopathy (38.1% vs. 29.7%) whereas patients with EF >50% more often had hypertension (40.6% vs. 29.8%), hypertrophic cardiomyopathy (11.5% vs. 0.7%) and congenital heart disease (7.6% vs. 2.7%), all p>0.001. Cardiovascular death was the most common cause of death in all EF categories (about 55%). In a Cox proportional hazard model, patients with EF >50% had hazard ratio (HR) (95% CI) 10.6 (5.71–19.8), those with EF 40–49% 6.83 (4.43–10.5) and patients with EF<40% 7.97 (6.45–9.85) for all-cause mortality (NS). According to the conditional survival analysis patients aged 20, 25, 30, 35 and 40 years with EF<40% lost a median of 28.5, 26.6, 24.7, 22.2 and 20.1 "life years" whereas patients with EF>50% lost 32.3, 28.7, 26.1, 26.3 and 21.6 "life years" as presented in figure 1. Conclusion: HF patients <55 years with EF>50% had different coexisting conditions and higher mortality risk, although not significant when compared to patients with EF <40%. Moreover, compared to the general population patients with EF>50% lost more life years than patients with EF<40%. Funding Acknowledgement: Type of funding source: None